Copper(I) Phosphide Nanocrystals for In Situ Self‐Generation Magnetic Resonance Imaging‐Guided Photothermal‐Enhanced Chemodynamic Synergetic Therapy Resisting Deep‐Seated Tumor - Liu, Yang; Wu, Junduo; Jin, Yinhua; Zhen, Wenyao; Wang, Yinghui; Liu, Jianhua; Jin, Longhai; Zhang, Songtao; Zhao, Ying; Song, Shuyan; Yang, Yang; Zhang, Hongjie (Advanced functional materials, 2019)
Fe‐based Fenton agents can generate highly reactive and toxic hydroxyl radicals (·OH) in the tumor microenvironment (TME) for chemodynamic therapy (CDT) with high specificity. However, the strict condition (lower pH environment: 3–4) of the highly efficient Fenton reaction limits its practical application in the clinic. Development of new CDT agents more suitable for TME is significant and challenging. A highly efficient Cu(I)‐based CDT agent, copper(I) phosphide nanocrystals (CP NCs), which is more adaptable to the pH value of TME than Fe‐based agents, thereby producing more ·OH to trigger the apoptosis of cancer cells, is prepared. Moreover, the excess glutathione (GSH) in TME can reduce the Cu(II) produced by a Fenton‐like reaction to Cu(I), further increasing the generation rate of ·OH and relieving tumor antioxidant ability. Furthermore, owing to their strong absorption in the NIR II region, CP NCs exhibit an excellent photothermal conversion effect, which can further improve the Fenton reaction. What is more, CP NCs can act as in situ self‐generation magnetic resonance imaging (MRI) agents owing to the generation of paramagnetic Cu(II) in response to excess H2O2 in the TME. These properties may open up the exploration of copper‐based materials in clinical application of self‐generation imaging‐guided synergetic treatment. A highly efficient Fenton agent Cu3P nanocrystal is shown to have good photothermal performance in the NIR II biowindows, allowing the realization of deep‐penetration photothermal‐enhanced chemodynamic therapy (CDT) and photothermal therapy (PTT). Additionally, this agent integrates with in situ self‐generation magnetic resonance imaging (MRI), due to the generation of paramagnetic Cu(II) in response to the tumor microenvironment, which can be used for accurate tumor theranostics.